Compositionally graded joints between magnetically dissimilar alloys achieved through directed energy deposition. (September 2021) - Firdosy, Samad; Ury, Nicholas; Kustas, Andrew B.; Carroll, Jay D.; Pathare, Priya; Casias, Zachary; Tung, Daniel; Susan, Don; Bobbitt, N. Scott; Chandross, Michael; Borgonia, J.P.; Ravi, Vilupanur A.; et al.
Abstract: Compositionally graded cylinders comprising FeCo-2V, a soft magnetic alloy, and 316L stainless steel, were produced by directed energy deposition incorporating two different gradient lengths. Five distinct regions in the microstructure were observed in both the as-printed and annealed gradients. When normalized for the gradient length, the gradients showed similar grain size and microhardness profiles. In tensile tests, the as-printed samples failed in the 316L region with an effective total "composite" strain of 20-30% and overall strength approaching that of wrought 316L. The annealed samples failed in the FeCo-2V region. Neither exhibited failure in the gradient region. Molecular dynamics simulations were used to calculate tensile strength as a function of composition, showing good correlation to experimental trends but not absolute values. This work demonstrates the tunability of site-specific properties using blown powder directed energy deposition to gradually grade from FeCo-2V to 316L stainless steel in a monolithic component. Graphical Abstract: Image, graphical abstract